The Study of The History of Termiz by Researchers - Raimov Mamasoat Safar o‘g‘li (Genius Journals, 2023)
Historical studies show that many scholars have written about the ancient city of Termiz, which was inhabited by people who lived in a sedentary manner on the eve of the Mongol invasion in Central Asia. It is extremely difficult to imagine the history of Central Asia and the cultural development of the peoples of the region without the history and monuments of the city of Termiz. This ancient city, which has made a worthy contribution to the history of the world and continues to add to it, has experienced many exciting periods in its development stage, and for several thousands of years it has successfully resisted the attacks of foreign enemies and became “Madinat ul-Rijal” (City of Heroes). Perhaps for this reason, the city of Termiz has always attracted the attention of world historians and scientists, great scholars.
Keywords: Central Asia; Old Termiz; Madinat ul-Rijal